To find the zeros of the quadratic function \( y = x^2 + 15x + 36 \), we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In this case, the coefficients are:
- \( a = 1 \)
- \( b = 15 \)
- \( c = 36 \)
Now, we can plug these values into the formula:
-
Calculate the discriminant: \[ b^2 - 4ac = 15^2 - 4 \cdot 1 \cdot 36 = 225 - 144 = 81 \]
-
Use the quadratic formula: \[ x = \frac{-15 \pm \sqrt{81}}{2 \cdot 1} = \frac{-15 \pm 9}{2} \]
-
Calculate the two possible values for \( x \):
- For the positive case: \[ x = \frac{-15 + 9}{2} = \frac{-6}{2} = -3 \]
- For the negative case: \[ x = \frac{-15 - 9}{2} = \frac{-24}{2} = -12 \]
Now, we have the two zeros of the quadratic function:
- Smaller zero: \( x = -12 \)
- Greater zero: \( x = -3 \)
So, the final result is:
- Smaller zero: \( x = -12 \)
- Greater zero: \( x = -3 \)